The experiences of adolescents and young adults residing with their families in emergency shelters in Canada. Issue 2 (3rd July 2018) - Polillo, Alexia; Sylvestre, John; Kerman, Nick; Lee, Catherine M.; Aubry, Tim; Czechowski, Konrad
ABSTRACT: Emergency homeless shelters can be stressful environments for families. They can be associated with emotional distress and feelings of restriction for parents, and with behavioural, social, and developmental challenges for children. However, little is known about the experiences of accompanied youth residing in shelter with their families, as the literature about this age group's experiences of homelessness has mainly focused on unaccompanied youth. Findings from the current study are drawn from qualitative interviews with 16 adolescents and young adults (aged 16–21) who were homeless and living with their families in family homeless shelters in Ottawa, Ontario, Canada. Youth described family homeless shelters as stressful environments but also found that the shelters provided support to them and their families. Youth discussed the various strategies they used to cope in facing the challenges of shelter life. These findings add to our understanding of youth who are homeless and highlight the ways in which they adapt to the challenges of living in a family homeless shelter with their families. Recommendations are included for ways that shelter staff and policymakers can enact operational and systemic changes that could potentially improve the experiences of such youth and their families.